2012
DOI: 10.1111/j.1365-2982.2012.01888.x
|View full text |Cite
|
Sign up to set email alerts
|

PPI therapy is equally effective in well‐defined non‐erosive reflux disease and in reflux esophagitis: a meta‐analysis

Abstract: Background Symptomatic response to proton pump inhibitor (PPI) therapy in patients with non-erosive reflux disease (NERD) is often reported as lower than in patients with erosive reflux disease (ERD). However, the definition of NERD differs across clinical trials. This meta-analysis aims to estimate the rate of symptom relief in response to PPI in NERD patients. Methods MEDLINE (1966, Cochrane Comprehensive Trial Register (1997 and EMBASE (1985EMBASE ( -2010 databases were searched and manual searches from stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(99 citation statements)
references
References 97 publications
5
83
0
11
Order By: Relevance
“…Since NERD is well defined in the Rome IV criteria, PPI therapy was almost equally effective among patients with real NERD and RE in the current study, which was consistent with other previous studies. 31 Excessive esophageal acid exposure is the main pathophysiological mechanism of real GERD, whereas visceral hypersensitivity is more prominent for RH and FH. 32 This can explain, to some extent, the lower responsiveness of routine PPI treatment among RH and FH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since NERD is well defined in the Rome IV criteria, PPI therapy was almost equally effective among patients with real NERD and RE in the current study, which was consistent with other previous studies. 31 Excessive esophageal acid exposure is the main pathophysiological mechanism of real GERD, whereas visceral hypersensitivity is more prominent for RH and FH. 32 This can explain, to some extent, the lower responsiveness of routine PPI treatment among RH and FH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Currently about 20% to 30% GERD patients have inadequate response to the proton pump inhibitor (PPI) treatment. 10 Esophageal baseline impedance may become a candidate as a predictor for treatment efficacy due to the potential association with the severity of acid exposure, but there is still lack of sufficient evidence to support this hypothesis. Thus, the aims of the current study are (1) to define the baseline impedance pattern of NERD patients, (2) to assess whether the baseline impedance correlated to the severity of esophageal acid exposure and DIS, and (3) to find out whether DIS and the baseline impedance can predict on the efficacy of PPI treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is important to emphasize that weakly acidic reflux is not synonymous with bile reflux. A simultaneous Bilitech and MII-pH study showed no relationship between the percentage of time for bilirubin 77 February 15, 2016|Volume 7|Issue 1| WJGP|www.wjgnet.com absorbance and weakly acidic or weakly alkaline reflux. Indeed, this study showed that the greatest number of bile refluxes occurred concomitantly with acid refluxes [82] .…”
Section: Multichannel Intraluminal Impedance and Phmentioning
confidence: 99%
“…Overall, it is notable that NERD patients vary greatly from a pathophysiological point of view and should be accurately studied by means of MII-pH to undertake the best therapeutic approach [6] . Indeed, a meta-analysis found that the once defined low response rate in NERD was likely the result of the inclusion of patients with heartburn who did not have reflux disease [77] . Recently, the ability to perform MII-pH testing to understand GERD pathophysiology better has improved through the introduction of up and coming parameters, such as the post-reflux swallow-induced peristaltic wave (PSPW) index, which indicates the efficacy of esophageal clearance [78] , and baseline impedance values, which indicate the presence of a lack of integrity in the esophageal mucosa [79] .…”
Section: Multichannel Intraluminal Impedance and Phmentioning
confidence: 99%